Phosphorus–Boron‐Based Polymers Obtained by Dehydrocoupling of Ferrocenylphosphine–Borane Adducts. Issue 14 (13th March 2014) - Pandey, Souvik; Lönnecke, Peter; Hey‐Hawkins, Evamarie
Abstract: Dehydrocoupling of the ferrocenylphosphine–borane adducts [FcPH2 (BH3 )] (1 ) [Fc = Fe(C5 H5 )(C5 H4 )] and [FcCH2 PH2 (BH3 )] (2 ) with [{Rh(μ‐Cl)(cod)}2 ] (cod = 1, 5‐cyclooctadiene) as catalyst gave the corresponding phosphorus–boron‐based polymers [FcPH(BH2 )] n (3 ) and [FcCH2 PH(BH2 )] n (4 ) as low‐ (heating in toluene, 3 low and4 low ) or high‐molecular‐weight (heating without solvent, 3 high or4 high ) poly(ferrocenylphosphinoborane)s depending on the reaction conditions. Dehydrocoupling of a racemic mixture of [2‐ N, N ‐dimethyl( N ‐borane)aminomethyl‐1‐ferrocenyl]phosphine–borane (6 ) resulted in several products, as both BH3 moieties are apparently involved in polymer formation. Quaternization of the amino group in planar‐chiral [Fe(C5 H5 ){C5 H3 (CH2 NMe2 )PH2 }] (5 ) with MeI and treatment of the corresponding ammonium salt [Fe(C5 H5 ){C5 H3 (CH2 NMe3 )PH2 }]I (8 ) with BH3 (THF) gave [Fe(C5 H5 ){C5 H3 (CH2 NMe3 )PH2 (BH3 )}]I (9 ), which proved to be a suitable precursor for selective dehydrocoupling to yield an ionic polymer, namely, {[Fe(C5 H5 ){C5 H3 (CH2 NMe3 )PH(BH2 )}]I} n . The ferrocenylphosphine–borane adducts1, 2, and6 were characterized by 31 P, 11 B, 1 H, and 13 C NMR spectroscopy, and the polymers were characterized by multinuclear NMR and IR spectroscopy, gel permeation chromatography (GPC), and thermal analysis [differential thermal analysis (DTA)/thermogravimetry (TG)]. The ionic precursor9 and the resulting polymer are highly insoluble and were characterized by solid‐state 31 P NMR spectroscopy, IR spectroscopy, and thermal analysis. Molecular structures of1, 6, 8, and9 were determined by X‐ray crystallography. Abstract : A new class of phosphine–borane adducts with ferrocenyl substituents, including the depicted ionic monomer containing a planar‐chiral ferrocene moiety, was prepared and employed in transition‐metal‐catalyzed dehydrocoupling {with [{Rh(μ‐Cl)(1, 5‐cod)}2] (cod = 1, 5‐cyclooctadiene) as catalyst} to give the first ferrocenyl‐substituted poly(phosphinoboranes).